A new look at the controllability cost of linear evolution systems with a long gaze at localized data - Bianchini, Roberta; Laheurte, Vincent; Sueur, Frank (Comptes Rendus. Mathématique)
We revisit the classical issue of the controllability/observability cost of linear first order evolution systems, starting with ODEs, before turning to some linear first order evolution PDEs in several space dimensions, including hyperbolic systems and pseudo-differential systems obtained by linearization in fluid mechanics. In particular we investigate the cost for localized initial data and, in the dispersive case, for initial data which are semiclassically microlocalized.